PENGGUNAAN TIKAR PERTUMBUHAN DALAM DETEKSI DINI STUNTING PADA BALITA DI DESA SUNGAI TUAN ULU - Iis Pusparina; Dewi Irianti; Filia Sofiani Ikasari (Bajang Institute, 2022)
Stunting is still an unresolved problem in Indonesia. Stunting itself is a condition of failure to thrive caused by chronic malnutrition so that toddlers are too short for their age. Early detection of stunting is one of the secondary prevention efforts that can be done by the community to identify stunting toddlers. The Posyandu in Sungai Tuan Ulu Village has never carried out early stunting detection. Early detection of stunting is now easier using a growth mat, which is a medium for measuring the suitability of a toddler's height with his age. This service activity aims to carry out early detection of stunting in toddlers using growth mats. The method used was atmosphere building. The target number of activities were 35 children under five who visit the Posyandu in Sungai Tuan Ulu Village. Service activities include coordinating with village heads, introducing growth mats to posyandu cadres, measuring toddlers' height using growth mats and handing over growth mats to posyandu cadres. The results obtained were from 24 childrens under five who were measured, 2 under-fives were in the red zone and 22 under-five were in the green zone.